The resting cyst of dinoflagellate Scrippsiella acuminata host bacterial microbiomes with more diverse trophic strategies under conditions typically observed in marine sediments - Deng, Yunyan; Li, Fengting; Shang, Lixia; Hu, Zhangxi; Yue, Caixia; Tang, Ying Zhong (Frontiers in Microbiology, 2024)
Variation in the condition of marine sediments provides selective preservation milieus, which act as a key determinant for the abundance and distribution of dinoflagellate resting cysts in natural sediments. Microbial degradation is an understudied biological factor of potential importance in the processes. However, gaps remain in our knowledge about the fundamental information of the bacterial consortia associated with dinoflagellate resting cysts both in laboratory cultures and in the field. Here we used Scrippsiella acuminata as a representative of cyst-producing dinoflagellates to delineate the diversity and composition of bacterial microbiomes co-existing with the laboratory-cultured resting cysts, and to explore possible impacts of low temperature, darkness, and anoxia (the mock conditions commonly observed in marine sediments) on the associated bacterial consortia. Bacterial microbiome with high diversity were revealed associated with S. acuminata at resting stage. The mock conditions could significantly shift bacterial community structure and exert notably inhibitory effects on growth-promoting bacteria. Resting cysts under conditions typically observed in marine sediments fostered bacterial microbiomes with more diverse trophic strategies, characteristic of prominently enriched anaerobic chemotrophic bacteria generating energy via respiration with several different terminal electron acceptors, which yielded more acidic milieu unfavorable for the preservation of calcareous resting cysts. Our findings suggest that there is complex and dynamic interaction between dinoflagellates resting cysts and the associated bacterial consortia in natural sediments. This intrinsic interaction may influence the maintenance and/or accumulation of dinoflagellate resting cysts with potential of germination and initiation blooms in the field.